A Design for Controllability Methodology for PEM Fuel Cells including the effect of Material Surface Defects on the Dynamic System Performance (2019)
Electric power has become indispensable for the development of society. Our quality of life is entirely dependent on the availability of electric energy in the industrial, commercial, and residential sectors. Most of this energy is currently obtained from non-renewable sources (oil, natural gas, and coal mainly). Unfortunately, the continuous combustion of these fuels has severely impacted the environment due to the continuous emissions of greenhouse gases. Therefore, the need to explore alternative energy sources in a wide array of applications is essential for the sustainability of our way of life. Hydrogen is one of the promising fuels of the future, which would allow a transition to a cleaner generation matrix. Although hydrogen is mostly obtained from reforming of natural gas, different pathways from renewable resources are developed and being researched. Therefore, the study of devices operating with hydrogen contributes to the construction of a sustainable future. Fuel cells are one of the most effective ways to transform hydrogen into electrical power. By definition, a fuel cell is an electrochemical device capable of producing electrical energy from a fuel and an oxidant. For Proton Exchange Membrane (PEM) fuel cells the fuel is hydrogen, which is supplied to the anode, and the oxidant agent is oxygen (or air) supplied to the cathode. In this research, a methodology is developed for the selection of fuel cells materials, considering how their properties influence the cell dynamic response. To achieve this, a test bench was designed and constructed to characterize the PEM fuel cells dynamic response, and laboratory tests were developed to perform defect characterization. Different membrane assemblies were tested to analyze the impact of their properties on the cell settling time, and therefore, determine its effect on the controllability of the system.